2022
DOI: 10.15541/jim20220265
|View full text |Cite
|
Sign up to set email alerts
|

Molten Salt Corrosion Behaviors and Mechanisms of Ytterbium Silicate Environmental Barrier Coating

Abstract: Environmental barrier coating (EBC) is essential for protection of ceramic matrix composite hot-sections in future gas turbine engines with high thrust-to-weight ratio. Rare-earth silicates, such as Yb 2 SiO 5 and Yb 2 Si 2 O 7 , have been developed for potential application as EBC. However, the corrosion behaviors and mechanisms of EBC in molten salt environment such as Na 2 SO 4 at high temperature are not clear. In this work, the Yb 2 SiO 5 /Yb 2 Si 2 O 7 /Si coating was prepared by vacuum plasma spraying (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…14,15,22,23 Rare earth disilicates (RE 2 Si 2 O 7 ) are considered the suitable materials of the EBCs, owing to their moderate mechanical/thermal properties and good corrosion resistance. [24][25][26][27][28][29][30] RE 2 Si 2 O 7 with different rare earth elements shows multiple crystal phases at different temperatures. 31 During the service, phase transformation may result in the volume changes, which will lead to the formation of cracks in the EBCs and accelerate the failure of the coatings.…”
Section: Introductionmentioning
confidence: 99%
“…14,15,22,23 Rare earth disilicates (RE 2 Si 2 O 7 ) are considered the suitable materials of the EBCs, owing to their moderate mechanical/thermal properties and good corrosion resistance. [24][25][26][27][28][29][30] RE 2 Si 2 O 7 with different rare earth elements shows multiple crystal phases at different temperatures. 31 During the service, phase transformation may result in the volume changes, which will lead to the formation of cracks in the EBCs and accelerate the failure of the coatings.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Rare-earth (RE) silicates are considered as promising novel E/TBC candidates, which exhibit excellent mechanical properties and thermal properties, such as low modulus, good damage tolerance, low thermal conductivity, coefficient of thermal expansion (CTE), and so on. [3][4][5][6][7] Among all silicates, lutetium silicates are widely studied owing to their excellent CMAS corrosion resistance and similar CTE values with SiC and mullite. 8 Tian et al observed that Lu 2 SiO 5 has excellent hightemperature durability and low thermal conductivity (1.72 W ⋅ m −1 ⋅ K −1 at 1273 K).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental/thermal barrier coatings (E/TBCs) are used to protect silicon‐based ceramic matrix composites (CMCs) substrates in aerospace engines from oxidation and corrosion, prolonging the service life of engine components 1,2 . Rare‐earth ( RE ) silicates are considered as promising novel E/TBC candidates, which exhibit excellent mechanical properties and thermal properties, such as low modulus, good damage tolerance, low thermal conductivity, coefficient of thermal expansion (CTE), and so on 3–7 . Among all silicates, lutetium silicates are widely studied owing to their excellent CMAS corrosion resistance and similar CTE values with SiC and mullite 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Yb 2 SiO 5 and Lu 2 SiO 5 are considered promising candidates for the EBC materials because they are excellent in resisting molten CMAS and water vapor and show low thermal conductivity (1.7-4.6 W/(m k)), compatible thermal expansion coefficients, and good chemical compatibility with CMCs substrates. [25][26][27][28][29][30][31][32][33] For example, Tian et al found that Yb 2 SiO 5 and Lu 2 SiO 5 which are high in internal friction can help build up the damage tolerance and passivate the cracks of the materials. 18 Zhao et al proved that Yb 2 SiO 5 /Yb 2 SiO 7 coatings demonstrate good resistance against the CMAS corrosion attack.…”
Section: Introductionmentioning
confidence: 99%
“…These factors make it impossible for them to become the perfect EBC in the real setting. Yb 2 SiO 5 and Lu 2 SiO 5 are considered promising candidates for the EBC materials because they are excellent in resisting molten CMAS and water vapor and show low thermal conductivity (1.7–4.6 W/(m k)), compatible thermal expansion coefficients, and good chemical compatibility with CMCs substrates 25–33 . For example, Tian et al.…”
Section: Introductionmentioning
confidence: 99%